2017
DOI: 10.3390/ijms18081666
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor-4 Inhibitor TAK-242 Attenuates Motor Dysfunction and Spinal Cord Pathology in an Amyotrophic Lateral Sclerosis Mouse Model

Abstract: Neuroinflammation contributes to amyotrophic lateral sclerosis (ALS) progression. TLR4, a transmembrane protein that plays a central role in activation of the innate immune system, has been shown to induce microglial activation in ALS models. TLR4 is up-regulated in the spinal cords of hSOD1G93A mice. We aimed to examine the effects of specific TLR4 inhibition on disease progression and survival in the hSOD1G93A mouse model of ALS. Immunologic effect of TLR4 inhibition in vitro was measured by the effect of TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 41 publications
(79 reference statements)
1
28
0
Order By: Relevance
“…LPS is a bacterial endotoxin that stimulates microglia for the production of NO and many proinflammatory cytokines such as tumor necrosis factor and interleukins (Kirkley et al, 2017). Those proinflammatory cytokines have been widely reported to cause neuroinflammation, lead to neuron death, and deteriorate PD pathology in several animal models (Fellner et al, 2017;Subedi et al, 2017). Src activation is driven in inflammatory cells by proinflammatory cytokines (Yeh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…LPS is a bacterial endotoxin that stimulates microglia for the production of NO and many proinflammatory cytokines such as tumor necrosis factor and interleukins (Kirkley et al, 2017). Those proinflammatory cytokines have been widely reported to cause neuroinflammation, lead to neuron death, and deteriorate PD pathology in several animal models (Fellner et al, 2017;Subedi et al, 2017). Src activation is driven in inflammatory cells by proinflammatory cytokines (Yeh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a prominent cell wall component of gram-negative bacteria that is a strong stimulator of microglial activation [ 6 ]. LPS-induced microglial activation results in inflammatory responses that promote disease progression in models of neurodegeneration [ 7 , 8 ]. LPS interacts with Toll-like receptors (TLRs) such as TLR4 on the surface of microglia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that many proteins contributing to inflammation and/or the innate immune system may exhibit high levels in the CSF, plasma, or tissues of ALS patients (e.g., tumor necrosis factor alpha (TNF-α), circulating chemokines, and cytokines). Among them, toll-like receptors (TLRs) have an important part in the formation of chronic inflammation in neurodegenerative illnesses such as ALS [ 7 ]. It has also been stated that ALS patients present signs of systemic inflammation, reflected in increased levels of C-reactive protein (CRP) and complement components, such as C3 and C4 [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%